Isolated metastasis of lung cancer to carpal bones - Stanković, Milan S; Lalić, Ivica R; Đuričin, Aleksandar P; Gvozdenović, Nemanja M (Vojnosanitetski pregled, 2017)
Introduction. Lung cancer often gives metastases in the bone system, of which the wrist accounts for 0.1% and the bones of the wrist are primarily affected in only 17% of cases. We presented a patient with the delayed diagnosis and a rare localization of isolated metastases of lung cancer to carpal bones which ended with upper arm amputation. Case report. A 56-year-old, a laborer, healthy, smoker, coughing for decades with occasional expectoration, hoarseness, during the last 3 months felt pain in his right wrist. He denied trauma. Physical examination led to the diagnosis of tendovaginitis of the hand. He visited a physiatrist and began treatment. After the therapy, symptoms were partially decreased and later began to worsen with symptoms of the median nerve compression. The neurologist diagnosed it as the carpal tunnel syndrome. The patient’s condition worsened and he was sent to the Emergency Center of the Clinical Center of Vojvodina, Novi Sad, Serbia with the diagnosis of arthritis of the wrist. The final diagnosis of lung adenocarcinoma with isolated metastasis to bone tissue was made with a biopsy of the tumor and examination by an oncologist. Primary tumor localization was diagnosed with a computed tomography (CT) scan and skeletal scintigraphy. The patient underwent upper arm amputation and was sent to an oncologist. Conclusion. Carefully taken anamnesis, detailed general and local examination, and frequent monitoring of patients could help make a correct diagnosis of this rare localization of the lung cancer, before the spreading process and the occurrence of severe complications.
Keywords: bone neoplasms; neoplasm metastasis wrist joint; carpal bones; lung neoplasms; diagnosis; treatment outcome